If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -7x = 8 + -1(4x + 6) Reorder the terms: 5 + -7x = 8 + -1(6 + 4x) 5 + -7x = 8 + (6 * -1 + 4x * -1) 5 + -7x = 8 + (-6 + -4x) Combine like terms: 8 + -6 = 2 5 + -7x = 2 + -4x Solving 5 + -7x = 2 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 5 + -7x + 4x = 2 + -4x + 4x Combine like terms: -7x + 4x = -3x 5 + -3x = 2 + -4x + 4x Combine like terms: -4x + 4x = 0 5 + -3x = 2 + 0 5 + -3x = 2 Add '-5' to each side of the equation. 5 + -5 + -3x = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 2 + -5 -3x = 2 + -5 Combine like terms: 2 + -5 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| 6x^2-6=7x-9 | | 4(-x+2)=8 | | 2y+x=5x+6 | | 15x^4/28yz^5 | | -4(2x+8)=16-6x | | 2w+15=4w+9 | | 80=.50(4.25) | | 3^=27^2/3 | | 448=6x^3*3 | | p+88=10p+52 | | -6x-5(-1-b)=19 | | (m-n+k)(m+9n-8k)=0 | | -9z-6-3=-16 | | 8x^2+10=-76 | | 14.75x=9.50x | | 3b-86=2b | | 2(x-2)=3(x-11) | | 22-14=4(x-6) | | x+44=5x | | 19x-26=7x+12 | | 9(5x+1)=5x-8c | | -1/4x=20 | | -7x-3x-7=17-2x | | 7f-4f=-35 | | t+69=2t | | 2y+6.9-4.2y-2.4y-3= | | y+78=2y | | 8x-9y=91 | | 20=1/4x | | -29-4k=-9(8k+7) | | 12/x-4=16 | | 5(-x-7)+3x=A |